Circular Noncoding RNA HIPK3 Mediates Retinal Vascular Dysfunction in Diabetes Mellitus. Issue 17 (24th October 2017) - Shan, Kun; Liu, Chang; Liu, Bai-Hui; Chen, Xue; Dong, Rui; Liu, Xin; Zhang, Yang-Yang; Liu, Ban; Zhang, Shu-Jie; Wang, Jia-Jian; Zhang, Sheng-Hai; Wu, Ji-Hong; et al.
Abstract : Background: The vascular complications of diabetes mellitus are the major causes of morbidity and mortality among people with diabetes. Circular RNAs are a class of endogenous noncoding RNAs that regulate gene expression in eukaryotes. In this study, we investigated the role of circular RNA in retinal vascular dysfunction induced by diabetes mellitus. Methods: Quantitative polymerase chain reactions, Sanger sequencing, and Northern blots were conducted to detect circular HIPK3 (circHIPK3) expression pattern on diabetes mellitus–related stresses. MTT (3-[4, 5-dimethythiazol-2-yl]-2, 5-diphenyl tetrazolium bromide) assays, EdU (5-ethynyl-2′-deoxyuridine) incorporation assays, Transwell migration assays, and Matrigel assays were conducted to detect the role of circHIPK3 in retinal endothelial cell function in vitro. Retinal trypsin digestion, vascular permeability assays, and ELISA assays were conducted to detect the role of circHIPK3 in retinal vascular dysfunction in vivo. Bioinformatics analysis, luciferase activity assays, RNA pull-down assays, and in vitro studies were conducted to reveal the mechanism of circHIPK3-mediated retinal vascular dysfunction. Results: circHIPK3 expression was significantly upregulated in diabetic retinas and retinal endothelial cells following stressors related to diabetes mellitus. circHIPK3 silencing or overexpressing circHIPK3 changed retinal endothelial cell viability, proliferation, migration, and tube formation in vitro. circHIPK3 silencing in vivo alleviated retinal vascular dysfunction, as shown by decreased retinal acellular capillaries, vascular leakage, and inflammation. circHIPK3 acted as an endogenous miR-30a-3p sponge to sequester and inhibit miR-30a-3p activity, which led to increased vascular endothelial growth factor-C, FZD4, and WNT2 expression. Ectopic expression of miR-30a-3p mimicked the effect of circHIPK3 silencing on vascular endothelial phenotypes in vivo and in vitro. Conclusions: The circular RNA circHIPK3 plays a role in diabetic retinopathy by blocking miR-30a function, leading to increased endothelial proliferation and vascular dysfunction. These data suggest that circular RNA is a potential target to control diabetic proliferative retinopathy. Abstract : Supplemental Digital Content is available in the text.